Codesign and community outreach to create COVID-19 safe communities: A Karen community case study - Davis, Hilary; Elmer, Shandell; Graves, Kaye; Learmonth, Caitlin (Frontiers in Public Health, 2023)
Government directives for health and community services during the COVID-19 pandemic centered on building capacity for COVID-19 safe behaviors. During 2020-2021 there was mounting pressure to increase vaccination numbers to boost population-wide immunity, thereby enabling the lessening of pandemic response restrictions. This community case study documents local experience in delivering information about COVID-safety and vaccination to a former refugee community (the Karen Community) in regional Victoria. Community outreach and codesign approaches established closer engagement between the Karen Community and Bendigo Community Health Services (BCHS). This case study is explored through semi-structured interviews conducted face-to-face and via videoconferencing with key Karen community leaders, Karen community members, vaccination clinic volunteers, and BCHS staff and bicultural workers. A hybrid approach that employed community outreach and codesign approaches in tandem built trust and closer ties between the Karen community and BCHS, which in turn led to increased understanding and compliance with COVID-safe messages and vaccination uptake. The community-led innovations included codesign of COVID-19 fact sheets and videos in Karen language, involvement of ‘local champions’, assisting Karen businesses with COVID-safe plans, and creation of a COVID-19 information hotline facilitated by BCHS bicultural staff. These innovations supported the delivery of vaccination clinics at the local Karen Temple. Embedding multi-level, tailored and responsive public health approaches is particularly important in complex settings where there are disproportionately high levels of community disadvantage, as occurred during the COVID-19 pandemic.